Mitochondrial complex III Qi‐site inhibitor resistance mutations found in laboratory selected mutants and field isolates. Issue 8 (24th December 2018) - Mounkoro, Pierre; Michel, Thomas; Benhachemi, Rafik; Surpateanu, Georgiana; Iorga, Bogdan I; Fisher, Nicholas; Meunier, Brigitte
Abstract: BACKGROUND: Complex III inhibitors targeting the Qi ‐site have been known for decades; some are used or being developed as antimicrobial compounds. Target site resistance mutations have been reported in laboratory‐selected mutants and in field isolates. Here, we present a brief overview of mutations found in laboratory‐selected resistant mutants. We also provide a study of mutations observed in field isolates of Plasmopara viticola, in particular the ametoctradin resistance substitution, S34L that we analysed in the yeast model. RESULTS: A survey of laboratory mutants showed that resistance could be caused by a large number of substitutions in the Qi ‐site. Four residues seemed key in term of resistance: N31, G37, L198 and K228. Using yeast, we analysed the effect of the ametoctradin resistance substitution S34L reported in field isolates of P. viticola . We showed that S34L caused a high level of resistance combined with a loss of complex III activity and growth competence. CONCLUSION: Use of single site Qi ‐site inhibitors is expected to result in the selection of resistant mutants. However, if the substitution is associated with a fitness penalty, as may be the case with S34L, resistance development might not be an insuperable obstacle, although careful monitoring is required. © 2018 Society of Chemical Industry Abstract : Mutations leading to mitochondrial complex III Qi ‐site inhibitor resistance in crop and human pathogens are catalogued, with special reference to the ametoctradin resistance mutation S34L studied in the yeast model.